2018
DOI: 10.1016/j.jorganchem.2018.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Mononuclear and dinuclear heteroleptic Cu(I) complexes based on pyridyl-triazole and DPEPhos with long-lived excited-state lifetimes

Abstract: A mononuclear and two dinuclear heteroleptic Cu(I) complexes have been successfully prepared, using the chelating bis[(2-diphenylphosphino)phenyl] ether (DPEPhos) and pyrid-2´-yl-1H-1,2,3-triazole as N^N chelating ligands. They show good luminescence in solution at room temperature with long-lived excited states. Furthermore, bimolecular quenching experiments of these new complexes with the catalyst Ni(cyclam)Cl2 encourage the use of such compounds as photosensitizers for the photoreduction of carbon dioxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 54 publications
2
27
0
Order By: Relevance
“…Needle-shaped crystals of 5b were obtained by the slow diffusion of cyclohexane into a concentrated solution in dichloromethane. The molecular structure of complex 5b was determined by X-ray diffraction, shown in Figure 3 , and agrees with heteroleptic Cu(I) complexes with similar ligands [ 40 , 41 ]. Bond valence sum analysis for Cu(1) in 5b gave a calculated oxidation state of 1.007 [ 42 ].…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Needle-shaped crystals of 5b were obtained by the slow diffusion of cyclohexane into a concentrated solution in dichloromethane. The molecular structure of complex 5b was determined by X-ray diffraction, shown in Figure 3 , and agrees with heteroleptic Cu(I) complexes with similar ligands [ 40 , 41 ]. Bond valence sum analysis for Cu(1) in 5b gave a calculated oxidation state of 1.007 [ 42 ].…”
Section: Resultssupporting
confidence: 55%
“…The low emission of Cu(I) complexes even in non-coordinating solvents, such as DCM, is attributed to the Jahn-Teller distortion that the complex undergoes upon excitation. The presence of the methyl substituent α to the pyridine might have impeded the distortion to some extent, as this was also demonstrated in other studies [40,[59][60][61]. Complex 5c presents a Φ of only 0.9%.…”
Section: In Solutionsupporting
confidence: 64%
“…This lability is correlated to the increased flexibility of NN, due to the presence of the methylene spacer between the quino(xa)line and triazole units, affecting the easiness of ligand exchange. Therefore, a comparison was done for the bond lengths and bite angles between complexes 1 – 4 and previously published Cu‐complexes with a related structure R 1 [11b] and R 2 [11a] ( cf . Figure 2) .…”
Section: Resultsmentioning
confidence: 99%
“…Although complexes 1 – 3 show negligible difference in bond lengths (Δ<0.06 Å), more significant differences are associated with the NN bite angles N 2 ‐Cu−N 4 (ca. 10°) in respect to R 1 [11b] and R 2 [11a] (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…[24] However, recent research has found that some dinuclear copper(I) complexes possess a more rigid molecular conformation and a smaller S1-T1 energy gap than mononuclear analogues, which would result in high PL and EL efficiencies. [25][26][27] Moreover, introduction of another metal atom can effectively enhance the SOC and further realize phosphorescence emission. [24] In pursuit of novel [Cu 2 (N N) 2 (P P) 2 ] 2 + complexes, we choose diphosphine compounds (Xantphos, Dppp and Binap) as the P P ligand, and N,N-diethylaniline-bridged triazol-pyridine (BPTA) as the N N ligand.…”
Section: Introductionmentioning
confidence: 99%